Identification of Student Conceptions on the Molecular Structure of Organic Compounds Using Question - Hulyadi Hulyadi; Muhali Muhali; Anita Fibonacci (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The atoms that make up organic molecules are carbon (C), hydrogen (H), oxygen (O), nitrogen (N), phosphorus (P), sulfur (S), and several other elements such as chlorine (Cl), bromine (Br), and iodine (I). The characteristics of the constituent organic molecules are important to study in order to understand the reactions and transformations in the synthesis of organic compounds. The weak conception of students about the characteristics of the constituent elements of organic compounds causes most students to experience difficulties in studying the structure of organic compounds. The purpose of this study was to find out the strengths and weaknesses of students' conceptions in understanding the molecular structure of organic compounds. This research is a quantitative descriptive research. The population of the study was 20 chemistry education students taking the basics of determining the structure of organic compounds. Samples were selected proportionally to the most. The instrument used is a description test designed in the form of a question mapping. The data obtained is then described in tables and graphs. The results showed that most of them were able to determine the types of atoms and bonds formed. Most students have not been able to explain the characteristics of the atoms that make up organic compounds and the subatomic characters that make up the atoms. Technology is needed that can visualize organic molecules at the atomic and subatomic levels to be able to build stronger student conceptions.